Between-session reliability of performance and asymmetry variables obtained during unilateral and bilateral countermovement jumps in basketball players - Pérez-Castilla, A.; García-Ramos, A.; Janicijevic, D.; Delgado-García, G.; De la Cruz, J. C.; Rojas, F. J.; Cepero, M. (PLOS ONE, 2021)
This study aimed to evaluate the between-session reliability of single-leg performance and asymmetry variables during unilateral and bilateral countermovement jumps (CMJ). Twenty-three basketball players completed two identical sessions which consisted of four unilateral CMJs (two with each leg) and two bilateral CMJs. Mean and peak values of force, velocity and power, impulse, and jump height were obtained separately for each leg using a dual force platform. All performance variables presented an acceptable reliability (CVrange = 4.05-9.98%) with the exceptions of jump height for the unilateral CMJs and mean power, peak velocity, peak power, and impulse for the left leg during the bilateral CMJ (CV=11.0%). Nine out of 14 variables were obtained with higher reliability during the unilateral CMJ (CVratio=1.16), and 4 out of 14 during the bilateral CMJ (CVratio=1.32). Asymmetry variables always showed an unacceptable reliability (ICCrange = 0.15-0.64) and poor/slight levels of agreement in direction (Kapparange = -0.10 to 0.15) for the unilateral CMJ, while an acceptable reliability (ICCrange = 0.74-0.77) and substantial levels of agreement in direction (Kapparange = 0.65 to 0.74) were generally obtained for the bilateral CMJ. These results suggest that single-leg performance can be obtained with higher reliability during the unilateral CMJ, while the bilateral CMJ provides more consistent measures of inter-limb asymmetries.